2008
DOI: 10.1177/0011000008319986
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural Competence and Social Justice Training in Counseling Psychology and Counselor Education

Abstract: This article presents the findings of a descriptive content analysis of 54 multicultural and diversity-related course syllabi drawn from counseling and counseling psychology programs accredited by the American Psychological Association and the Accreditation of Counseling and Related Programs. Results suggest that most courses adhere to the knowledge, awareness, and skills paradigm of multicultural competence. However, actual course content varies considerably. Whereas the findings identify social justice conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
212
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(223 citation statements)
references
References 31 publications
(37 reference statements)
7
212
1
3
Order By: Relevance
“…Although this is consistent with findings in other mental health training programs (Green et al, 2009;Malott, Paone, Maddux, & Rothman, 2010;McCabe & Rubinson, 2008;Savage et al, 2004), such practices lag behind best practice in multicultural training (McHaelen, 2006;T. B. Smith, Constantine, Dunn, Dinehwart, & Montoya, 2006).…”
Section: Discussionsupporting
confidence: 84%
“…Although this is consistent with findings in other mental health training programs (Green et al, 2009;Malott, Paone, Maddux, & Rothman, 2010;McCabe & Rubinson, 2008;Savage et al, 2004), such practices lag behind best practice in multicultural training (McHaelen, 2006;T. B. Smith, Constantine, Dunn, Dinehwart, & Montoya, 2006).…”
Section: Discussionsupporting
confidence: 84%
“…There is evidence that MCC training is being taught in higher education (Stebnicki & Cubero, 2008;Pieterse, Evans, Risner-Butner, Collins, & Mason, 2009), however, there is a need to improve multicultural training definitions (Cumming-McCann & Accordino, 2005) that would assist in training applied to counseling center programs. Competent multicultural counseling is a mainstay for centers to provide ethical counseling services.…”
Section: Discussionmentioning
confidence: 99%
“…New directions include the formation of advocacy to competent multicultural counselor repertoires. Specifically, multiculturalism as a movement has moved into the realm of social justice, where counselors are now encouraged not only to be competent counselors, but effective advocates for people from diverse populations inside and outside of the counseling office (Pieterse et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Extrapolating the concept of teaching multiculturalism via single course, Pieterse, Evans, Ristner-Butner, Collins, and Mason (2009) conducted a descriptive content analysis of 54 multicultural and diversity-related course syllabi from diverse counseling and counseling psychology programs accredited by the American Psychological Association (APA) and the Council of Accreditation of Counseling and Related Programs (CACREP). They reported that the majority of the courses observe the multicultural paradigm of development of knowledge, awareness, and skills.…”
Section: Single Multicultural Course -Explicit Curriculum Designmentioning
confidence: 99%